On the positive colored noise of the price of stock - Kananthai A. (2017)
© 2016 by the Mathematical Association of Thailand. All rights reserved. In studying the fluctuation of the price of stock, there are three pa- rameters affecting such fluctuation. The first is well known parameter which is known as the volatility of stock. The second is not really well know which is white noise and has not been computed. Fortunately, in this paper we can find the for- mula of such white noise and can be computed. The third parameter is the positive colored noise which is the aim of this paper. Such positive colored noise is derived from the white noise and it is interesting parameter particularly, in involving the infinitely fluctuation of the price of stock. Moreover, The relationships between three parameter has been also studied and obtaining the interesting results.